Taxonomic Assessment on the Six New Records of Bulbophyllum Thour. (Orchidaceae) for Darjeeling Himalaya of West Bengal, India - Yonzone, Rajendra; Lama, D.; Bhujel, R. B.; Rai, Samuel (Indian Forester, 2015)
Present paper deals with six taxa of the genus Bulbophyllum Thour. (Orchidaceae) as new records for Darjeeling Himalaya of West Bengal, namely Bulbophyllum affine Lindl., B. appendiculatum (Rolfe) J.J. Smith, B. bisetum Lindl., B. helenae (Kuntze) J.J. Smith, B. scabratum Rchb. f., and B. crassipes Hook. f. An updated nomenclature, important synonyms, illustrated description, photographs, habitat, flowering and fruiting, altitudinal range, specimen examined, present status and geographical distribution for each species have also been given.